Population pharmacokinetic modeling and simulations of berotralstat for prophylactic treatment of attacks of hereditary angioedema. Issue 4 (25th February 2022) - Mathis, Amanda; Sale, Mark; Cornpropst, Melanie; Sheridan, William P.; Ma, Shu Chin
Abstract: Hereditary angioedema (HAE) is an autosomal dominant disorder characterized by recurrent episodes of swelling of the skin, larynx, gastrointestinal tract, genitals, and extremities that can be disruptive to patient quality of life. Dysregulation of plasma kallikrein activity leads to increased production and accumulation of bradykinin in HAE and causes attacks of angioedema. Plasma kallikrein is a serine protease essential for the formation of bradykinin. Berotralstat is a potent, highly selective, orally bioavailable small‐molecule plasma kallikrein inhibitor that has been approved to prevent attacks of HAE in adults and children 12 years of age and older. Population pharmacokinetic (PK) analyses were conducted to describe the PK of berotralstat (BCX7353; Orladeyo ™ ) and to evaluate the covariates that may explain variability in PK. The PK of berotralstat were characterized by population PK modeling of data from 13 clinical studies and a total of 771 healthy subjects and patients with HAE. The PK profile was well described by a three‐compartment model with first‐order absorption including an absorption lag time and linear elimination. Among the covariates tested, the effects of bilirubin and food were found not to be clinically significant and were removed from the model. Covariate analysis indicated significant effects of dose on bioavailability and weight on berotralstat clearance and volume. Despite the covariate effect of weight, simulations in adolescents and adults who were underweight, low weight, and overweight demonstrated similar predicted exposures to those observed at therapeutic doses in a clinical trial. Therefore, no dose adjustment is required in these HAE patient subpopulations.